الأمن الصحي في إقليم كوردستان -العراق (دراسة في الجغرافية السياسية) - البوتاني, طلعت محمد طاهر عمر (Sulaimani Journal for Humanities, 2021)
Health security is one of the dimensions of human security in the Kurdistan region of Iraq, and the health sector is an important tool in building human beings physically and mentally and therefore has a positive impact on the strength of the state in terms of economic, education and social aspects. Human beings are the pillars of development and health is a complex process aimed at creating a healthy society and relying on infrastructure, human resources and scientific and technological and technical progress in providing health care to citizens, but health security and health sector in Kurdistan region of Iraq has suffered and hasn’t progressed but declined as a result of "the wars that have been going on since the second decade of the twentieth century and political instability, led to the deterioration of this vital sector, and it has had a negative impact on the strength of the region in the provision of health services. This study has used health indicators and compared them with developing and developed countries, to assess health security in the region, and the study has shown that the health sector has a lot of weaknesses, and this requires the regional government to develop a strategy that has a vision of the future based on modern plans and programs to revive this vital sector.
Keywords: Kurdistan Region; Health Security; Health services; Sustainable Development; Scientific development